2018
DOI: 10.3390/s18020424
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Surface-Enhanced Raman Spectroscopic Method for on-Site Screening of Tetracycline Residue in Whole Milk

Abstract: Therapeutic and subtherapeutic use of veterinary drugs has increased the risk of residue contamination in animal food products. Antibiotics such as tetracycline are used for mastitis treatment of lactating cows. Milk expressed from treated cows before the withdrawal period has elapsed may contain tetracycline residue. This study developed a simple surface-enhanced Raman spectroscopic (SERS) method for on-site screening of tetracycline residue in milk and water. Six batches of silver colloid nanoparticles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 54 publications
(53 reference statements)
2
33
0
Order By: Relevance
“…When antibiotics are used, dairymen should follow specific protocols to prevent the prevalence of antibiotic residues in human milk. Despite that, reports show that there is still presence of antibiotics in milk, above the recommended values 1,6 . Their relative stability to the pasteurization processes and the high quantities of milk required to dilute milk from treated quarters, can cause monetary losses and technological problems to the dairy industry.…”
Section: Introductionmentioning
confidence: 95%
“…When antibiotics are used, dairymen should follow specific protocols to prevent the prevalence of antibiotic residues in human milk. Despite that, reports show that there is still presence of antibiotics in milk, above the recommended values 1,6 . Their relative stability to the pasteurization processes and the high quantities of milk required to dilute milk from treated quarters, can cause monetary losses and technological problems to the dairy industry.…”
Section: Introductionmentioning
confidence: 95%
“…For instance, pesticide residues or illegal additives should be screened before exposure to consumers. [11][12][13][14] Explosives and drugs on luggage and clothing should be detected quickly and efficiently to avoid large numbers of passengers being stranded. [15,16] In the field of archaeological or cultural heritage studies, research on cultural heritage should be stringently noninvasive and nondestructive.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, due to narrow well-resolved bands characteristic of inelastic light scattering, SERS can provide abundant vibrational information of the adsorbed molecules and be applied to multiplex detection. In fact, this technique has been explored for the TC detection in several types of samples [23,24,25,26,27,28,29,30,31]. For instance, Li et al have applied Au hollow spheres to detect TC and the limit of detection reached 0.1 μg/L [31].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al have applied Au hollow spheres to detect TC and the limit of detection reached 0.1 μg/L [31]. Dhakal et al have reported a cyclodextrin-modified Ag colloid for on-site quantification of TC residues in whole milk, achieving a detection limit of 0.01 ppm, which is below the maximum residue limit (MRL) set by governmental authorities [27].…”
Section: Introductionmentioning
confidence: 99%